Using homogenization, sonication and thermo-sonication to inactivate fungi - Daniela Campaniello; Antonio Bevilacqua; Milena Sinigaglia; Maria Rosaria Corbo (PeerJ, 2016)
Ultrasound (US), Thermo-sonication (TS) and High Pressure Homogenization (HPH) were studied as tools to inactivate the spores of Penicillium spp. and Mucor spp. inoculated in distilled water. For US, the power ranged from 40% to 100%, pulse from 2 to 10 s, and duration of the treatment from 2 to 10 min. TS was performed combining US (40–80% of power, for 8 min and pulse of 2 s) with a thermal treatment (50, 55 and 60°C at 4, 8 and 12 min). Homogenization was done at 30–150 MPa for 1, 2 and 3 times. Power was the most important factors to determine the antifungal effect of US and TS towards the conidia of Penicillium spp.; on the other hand, in US treatments Mucor spp. was also affected by pulse and time. HPH exerted a significant antifungal effect only if the highest pressures were applied for 2–3 times.